Human Resources Strategies and Service Quality: Private Jordanian Hospitals Operating in the Northern Region - Al-Sarhan, Abdullah; Al-Awawda, Walid (The Arab Journal of Administration, 2022)
The aim of this study is to identify the impact of Human Resources Strategies on the service quality provided by Jordanian Private Hospitals. Five dimensions of the Human Resources Strategies were investigated: HR planning, selection and appointment, training and development, performance appraisal, incentives and rewards. Furthermore, five dimensions of the service quality were examined: response, reliability, tangibility, safety and empathy. A field study was conduct to cover the population of eight Jordanian Private Hospitals operating in the Northern Territory. A questionnaire was conduct to obtain data. The researcher distributed the questionnaire to fifteen employees in each Hospital. (120) questionnaires were distributed. Many statistical methods like Descriptive methods, Coefficients Regression, were use in this study. The study showed that the performance appraisal variable has the greatest impact on service quality indicators followed by incentives and rewards, then training and development, HR planning; selection and appointment were the lowest impact in quality service indicators. Based on the study outcomes, the researcher presents some recommendations for the Hospitals studied, and future researches.